A dynamic approach for evaluating the consequences of toxic gas dispersion in the chemical plants using CFD and evacuation modelling. (May 2020) - Wang, Jiyun; Yu, Xiaoyang; Zong, Ruowen
Abstract: Accidental releases of toxic gas in the chemical plants have caused significant harm to the exposed occupants. To evaluate the consequences of these accidents, a dynamic approach considering the gas dispersion and behavior evacuation modelling has been proposed in this paper. This approach is applied to a hypothetical scenario including an accidental chlorine release in a chemical plant. CFD technique is utilized to calculate the time-varying concentration filed and evacuation modelling is used to obtain the evacuation routes. The exposure concentrations in the evacuation routes are calculated by using the code of data query. The integrated concentration toxic load model and probit model are used to calculate the probability of mortality of each occupant by using the exposure concentrations. Based on this dynamic approach, a new concept of average probability of mortality (APM) has been proposed to quantify the consequences of different accidental scenarios. The results show that APM decreases when the required detection time decreases or emergency evacuation mode is implemented. The impact of the detection time on APM becomes small as the wind speed increases. The effect of emergency evacuation mode is more obvious when the release occurs in an outdoor space. Highlights: Dynamic approach considers gas dispersion and behavioral evacuation. A method to deal with data obtained from Fluent and Pathfinder is presented. A new concept of average probabilities of mortality (APM) is proposed. The effectiveness of risk mitigation measures is assessed by APM. One method to determine the best evacuation routes is proposed.